2010
DOI: 10.5194/nhess-10-647-2010
|View full text |Cite
|
Sign up to set email alerts
|

The 24 July 2008 outburst flood at the western Zyndan glacier lake and recent regional changes in glacier lakes of the Teskey Ala-Too range, Tien Shan, Kyrgyzstan

Abstract: The 24 July 2008 outburst flood at the western Zyndan glacier lake and recent regional changes in glacier lakes of the Teskey Ala-Too range,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
108
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(113 citation statements)
references
References 24 publications
5
108
0
Order By: Relevance
“…Hence, it could be expected that the number and area of potentially dangerous lakes increases in the study area, a fact which is confirmed by this study. Other studies on glacial lakes in the same and adjacent mountain ranges of the Tien Shan show similar results (Erohin and Cerny 2009;; Jansky et al 2011;; Narama et al 2009; Narama et al , 2010a; Popov 1988). Further glacier shrinkage will probably lead to higher danger of a GLOF.…”
Section: Potentially Dangerous Glacial Lakes (Pdgl)supporting
confidence: 72%
“…Hence, it could be expected that the number and area of potentially dangerous lakes increases in the study area, a fact which is confirmed by this study. Other studies on glacial lakes in the same and adjacent mountain ranges of the Tien Shan show similar results (Erohin and Cerny 2009;; Jansky et al 2011;; Narama et al 2009; Narama et al , 2010a; Popov 1988). Further glacier shrinkage will probably lead to higher danger of a GLOF.…”
Section: Potentially Dangerous Glacial Lakes (Pdgl)supporting
confidence: 72%
“…hazardous glacial lakes may evolve within less than one year. This phenomenon was illustrated not only by the Dasht event, but also by the outburst of the western Zyndan glacier lake in the Tien-Shan (Kyrgyzstan) in 2008 (Narama et al, 2010). This means that careful monitoring of the glacial environment is required in order to keep updated on developing hazards.…”
Section: Discussionmentioning
confidence: 99%
“…However, several events are known from the Tien Shan, most recently the outbursts of the Archa-Bashy glacier lake in 1998 and of the western Zyndan glacier lake in 2008 (Narama et al, 2010).…”
Section: The Dasht 2002 Eventmentioning
confidence: 99%
See 1 more Smart Citation
“…Very little is known or understood about groundwater in the Far North, or how it might be changing because observations are so sparse (Bense et al, 2009;Moran and Solin, 2006). There are considerable unknowns about the timing of glacial retreat, thawing of permafrost, and change in subsurface storage of water (Walsh et al, 2014;Murray et al, 2010).…”
Section: Estimating and Reducing Uncertaintymentioning
confidence: 99%